Marketing Strategies for Fabrication Operational Processes: The Case of Press Shop Sdn Bhd - Ho, Chee Poh; Marthadam, Baliah; Razmi, Bustaman Mazuki (2014)
Press Shop Sdn. Bhd. was established in 1995 in order to fulfill their contract obligation to their major customer, Rhombus Caster Sdn. Bhd. Throughout the year until now, their market dominated by fulfilling their contract job to Rhombus Caster with about 80% from total revenue. From literature we found that too much depending on major customer might jeopardized business sustainability as it could vanishing company revenue if something happen to major customer or major customer has change their business direction. From perspective of SMEs’ overview, local SMEs’ not really bother about business and marketing strategy.